Effects of total soy saponins on free radicals in the quadriceps femoris, serum testosterone, LDH, and BUN of exhausted rats - Zhigang Liu; Ruixin Nie; Yun Liu; Zhouhong Li; Chenxi Yang; Zhengying Xiong (Elsevier, 2017)
Purpose: The aim of this study was to investigate the impact of total soy saponins (TS) on the free radical metabolism from the quadriceps femoris muscle, serum testosterone, lactate dehydrogenase (LDH), and blood urea nitrogen (BUN) in rats exercised to exhaustion. Methods: A one-time exhausted treadmill exercise session was used. Sprague-Dawley rats were divided into 4 groups: a control group-animals receiving no TS and no exercise (NTSNE), animals receiving TS but no exercise group (TSNE), animals receiving no TS but exercised to exhaustion group (NTSE), and animals receiving TS and exercised to exhaustion group (TSE). The TSNE and TSE groups were fed TS at a dosage of 20 mg/kg body weight once per day for 2 weeks. The NTSE group was given a placebo, and the NTSNE group was not given any treatment. The NTSE and TSE groups were exercised at speed of 30 m/min on treadmill until exhausted. The exercise time and exercise distance were recorded when the rats became exhausted and the rats were then decapitated and anatomized immediately. A 10% homogenate of the quadriceps femoris tissue was prepared. The levels of superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA), glutathione peroxidase (GSH-Px), glutathione reductase (GR), reduced glutathione (GSH), total antioxidant capacity (T-AOC), LDH, BUN, and serum testosterone were tested. Results: TS significantly increased the exercise time to exhaustion by 20.62% (p < 0.05). The MDA levels were decreased significantly in the TSNE group than in NTSNE group (p < 0.05); the T-AOC levels increased significantly in the TSNE group than in the other 3 groups (p < 0.01, p < 0.05, p < 0.05). The LDH activity significantly increased in the NTSE group than in TSNE group (p < 0.05). The BUN levels significantly increased in the NTSE group than in the other 3 groups (p < 0.01, p < 0.01, p < 0.05), and significantly increased in the TSE group than in NTSNE and TSNE groups (both p < 0.01). The serum testosterone levels increased significantly in the TSNE group than in the other 3 groups (all p < 0.01). SOD, CAT, GSH-Px, GR, and GSH were not statistically different among the groups. Conclusion: TS can significantly improve the exercised rats' serum testosterone level and antioxidant activity in their quadriceps femoris to varying degrees, decrease MDA and serum LDH and BUN levels, increase the exercise time, and delay the occurrence of the fatigue.